Mainstream Early Childhood Teachers and Their Understandings of Pacific Education - Jattan, Jasmin (Auckland University of Technology, 2017)
Abstract This research explores the views of eight mainstream early childhood teachers and their understandings of Pacific education. Pacific children in education continue to fall within the underachievement statistics in Aotearoa, New Zealand. This has remained of consistent concern over several decades. The Government has put into effect strategies specifically targeted towards Pacific children in education to try and change this. Considerable pressure has been placed on teachers to ensure accountability within their teaching practice, to prove they are providing the quality education necessary for Pacific children to succeed. The methodology I use to gather information is qualitative, with the use of semi-structured interviews. The use of semi-structured interviews allowed for the voices of mainstream teachers to be captured and heard. It also allowed me to gain insight into their ideas and thoughts on quality for Pacific children as well as the very real challenges faced in their practice with Pacific children in early childhood education. The findings indicated the need for relevant and continued professional development to ensure teachers were supported in their practice within the area of Pacific education. The findings also indicated a lack of confidence in mainstream early childhood teachers in the area of Pacific education. This led to teachers having a dependence on Pacific teachers and perceiving Pacific teachers as the only answer to be able to provide the quality needed for Pacific children. In conclusion, the findings indicated the need for teachers to examine their ideas of quality for Pacific children and to move beyond basic understandings of Pacific children and people to be truly effective in their teaching practice to support the learning and development of Pacific children today.
Keywords: Early childhood education; Early childhood teachers; Pacific early childhood education; Mainstream early childhood education